Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12957-016-0832-6
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of selenium-binding protein 1 is associated with poor prognosis in lung squamous cell carcinoma

Abstract: BackgroundWe found that selenium-binding protein 1 (SBP1) was progressively decreased in the human bronchial epithelial carcinogenic processes. Knockdown of SBP1 in immortalized human bronchial epithelial cell line 16HBE cells significantly increased the efficiency of B[a]P-induced cell transformation. However, the relationship between SBP1 expression and clinicopathological factors of patients has not been defined completely. The specific role of SBP1 in prognosis of lung squamous cell carcinoma (LSCC) is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…In contrast with small cell lung cancer cells, the growth and division of NSCLC cells are much quicker, and their invasion to adjacent tissues and distant metastasis are much earlier [ 2 , 3 ]. More than half of the non-small cell lung tumors are diagnosed at advanced stages, so that the 5-year survival rate of NSCLC patients is lower than 15% [ 4–6 ]. The pathogenesis of NSCLC is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with small cell lung cancer cells, the growth and division of NSCLC cells are much quicker, and their invasion to adjacent tissues and distant metastasis are much earlier [ 2 , 3 ]. More than half of the non-small cell lung tumors are diagnosed at advanced stages, so that the 5-year survival rate of NSCLC patients is lower than 15% [ 4–6 ]. The pathogenesis of NSCLC is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that sodium selenite exhibited anti-proliferative activity by modulating various pathways including ERK activation (15)(16)(17)(18)(19). Sodium selenite could upregulate ERK expression at lower doses, while at higher doses it decreases ERK activation (27).…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer mechanism of selenium in thyroid cancer, however, has not been fully elucidated (13,14). Previous studies have suggested that the possible mechanism of action of selenite included stimulation of the immune system, activation of natural killer cells, inhibition of angiogenesis, enhancement of damaged DNA fragment repair, and initiation of apoptosis in various cancers (15)(16)(17)(18)(19). Recent studies further demonstrated that selenite suppressed cell differentiation through inhibiting ERK activation in vascular smooth muscle cells (20,21).…”
mentioning
confidence: 99%
“…Seleniumbinding proteins are known to play important roles in cancer prevention effects of selenium. Downregulation of SELENBP1 is associated with poor prognosis in NSCLC patients (Tan et al, 2016;Zeng et al, 2013). Overall, the proposed approach identifies more informative prognostic markers.…”
Section: Nsclc Datamentioning
confidence: 99%
“…They are TOP2A, ASPM, SELENBP1, MAD2L1, CDC20, PRC1, TYMS, and DLGAP5. Downregulation of SELENBP1 is associated with poor prognosis in NSCLC patients (Tan et al, 2016;Zeng et al, 2013). PRC1 (Protein regulator of Cytokinesis 1) has the highest correlation with PCLAF (r= 0.83).…”
Section: Nsclc Datamentioning
confidence: 99%